Synthesis and Antidepressant Activity of Pyrazoline Derivatives (Dhaka University Journal of Pharmaceutical Sciences, 2020)
In the present study a series of substituted pyrazolines (3a-f) has been synthesized by reacting chalcones (2a-f) and semicarbazide (1) in methanol medium. All the title compounds were assessed for their in-vivo anti-depressant activity by tail suspension test (TST) and forced swimming test (FST) methods. Compound 3a was found to exhibit moderate antidepressant activity in comparison to standard Imipramine. Newly synthesized compounds were characterized by mass (MS), 1H-NMR and infrared (IR) spectral analytical data.Dhaka Univ. J. Pharm. Sci. 19(2): 179-184, 2020 (December)